2018
DOI: 10.3390/molecules23010172
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Selection for Quantitative Real-Time Reverse-Transcriptase PCR in Annual Ryegrass (Lolium multiflorum) Subjected to Various Abiotic Stresses

Abstract: To select the most stable reference genes in annual ryegrass (Lolium multiflorum), we studied annual ryegrass leaf tissues exposed to various abiotic stresses by qRT-PCR and selected 11 candidate reference genes, i.e., 18S rRNA, E2, GAPDH, eIF4A, HIS3, SAMDC, TBP-1, Unigene71, Unigene77, Unigene755, and Unigene14912. We then used GeNorm, NormFinder, and BestKeeper to analyze the expression stability of these 11 genes, and used RefFinder to comprehensively rank genes according to stability. Under different stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…We found that the two algorithms produced the same ranking of the reference genes according to the differences in the stability (Table 2 and Fig. 3), which was consistent with previous studies [5,19]. The NormFinder analysis showed that HuUBQ and HuUQT were the two top stable reference genes in all of the experimental samples, while HuACT (under salt stress, drought stress, and different cultivars) and Hu18S rRNA (under heat stress and different tissues) were the most unstable reference genes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the two algorithms produced the same ranking of the reference genes according to the differences in the stability (Table 2 and Fig. 3), which was consistent with previous studies [5,19]. The NormFinder analysis showed that HuUBQ and HuUQT were the two top stable reference genes in all of the experimental samples, while HuACT (under salt stress, drought stress, and different cultivars) and Hu18S rRNA (under heat stress and different tissues) were the most unstable reference genes.…”
Section: Discussionsupporting
confidence: 91%
“…species, such as rice [14], rubber tree [15], sunflower [16], black locust [17], grapevine [18], and annual ryegrass [19]. species, such as rice [14], rubber tree [15], sunflower [16], black locust [17], grapevine [18], and annual ryegrass [19].…”
mentioning
confidence: 99%
“…Under nonstress conditions, HIS and EF1 was the best combination for data normalization in tissue samples (Table 3). In L. multi orum, HIS also showed a stable expression pattern under acidic aluminum stress and heavy metal stress, while it could not be selected as an internal control gene in Populus tomentosa due to its poor expression stability [26,48]. Under cold stress conditions, UBQ and EF1 were su cient for data normalization in P. edulis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used tools are geNorm, NormFinder and BestKeeper [20][21][22]. These three tools have been successfully used for the selection of reference genes in amaranth (Amaranthus tricolor), Setaria viridis, Carex rigescens, Lolium multi orum, Euscaphis konishii Hayata, P. massoniana, Alopecurus aequalis Sobol, Carica papaya L., Olea europaea L., Cucurbita pepo, Brassica napus, L. chinense and Populus [18,19,[23][24][25][26][27][28][29][30][31][32][33]. The use of multiple tools to select internal control genes for RT-qPCR data normalization has become a basic and indispensable process in the study of the expression patterns of functional genes.…”
Section: Introductionmentioning
confidence: 99%
“…It has many advantages such as high accuracy, specificity, low cost, and reproducibility [1]. However, the accuracy of qPCR results is influenced by the quality of RNA, efficiency of reverse transcription, primer specificity, sample volume, and amplification efficiency [2]. In order to improve this accuracy, it is important to introduce one or more reference genes for standard correction expression.…”
Section: Introductionmentioning
confidence: 99%